Cross-Sex Siblingship and Marriage: Transformations of Kinship Relations among the Wampar, Papua New Guinea - Beer, Bettina (Anthropologica, 2015)
Relations between brothers and sisters remain crucial to Wampar patterns of affinity and broader processes of social reproduction, despite a century of significant historical change. Nevertheless, the role that these ties play, under contemporary circumstances, contrasts in important ways with their former place in defining connections within and between corporate groups. Changes in partner choice, rates of interethnic marriage, concepts of intimacy, patterns of social stratification and household composition have all had effects on sibling bonds and their relevance to affinal relations. The effects of these factors are amplified by the Wampar’s proximity to the city of Lae.